Somos Más: How Racial Threat and Anger Mobilized Latino Voters in the Trump Era. (December 2019) - Gutierrez, Angela; Ocampo, Angela X.; Barreto, Matt A.; Segura, Gary
While evidence from California suggests that group threat mobilizes Latinos, nationally, there has never been a test case for this theory. In 2016, the Trump campaign provided a clear case of group threat through his divisive rhetoric and policy proposals targeting Mexican Americans and immigrants. Using the 2016 Collaborative Multi-Racial Post-Election Survey (CMPS) data, we find evidence that Latino voters were politically motivated by Trump's anti-Latino rhetoric. We hypothesize that Latino voters who perceive Latinos as a racialized group and feel a sense of immigrant-linked fate are more likely to hold negative views toward the Republican candidate, and feel angry during the 2016 election. We further find that Latino voters who were angry were more likely to engage in political activities such as donating to campaigns, contacting government officials, and protesting during and shortly after the 2016 election. The findings hold for U.S. born Latinos as well as among non-Mexican Latinos who felt similarly targeted by Trump's rhetoric and proposals.